Sparse image and signal processing : wavelets and related geometric multiscale analysis - Starck, Jean-Luc; Murtagh, Fionn; Fadili, Jalal (Cambridge : Cambridge University Press, 2015)
This thoroughly updated new edition presents state of the art sparse and multiscale image and signal processing. It covers linear multiscale geometric transforms, such as wavelet, ridgelet, or curvelet transforms, and non-linear multiscale transforms based on the median and mathematical morphology operators. Along with an up-to-the-minute description of required computation, it covers the latest results in inverse problem solving and regularization, sparse signal decomposition, blind source separation, in-painting, and compressed sensing. New chapters and sections cover multiscale geometric transforms for three-dimensional data (data cubes), data on the sphere (geo-located data), dictionary learning, and nonnegative matrix factorization. The authors wed theory and practice in examining applications in areas such as astronomy, including recent results from the European Space Agency's Herschel mission, biology, fusion physics, cold dark matter simulation, medical MRI, digital media, and forensics. MATLAB® and IDL code, available online at www.SparseSignalRecipes.info, accompany these methods and all applications.
Introduction to the world of sparsity -- The wavelet transform -- Redundant wavelet transform -- Nonlinear multiscale transforms -- Multiscale geometric transforms -- Sparsity and noise removal -- Linear inverse problems -- Morphological diversity -- Sparse blind source separation -- Dictionary learning -- Three-dimensional sparse representations -- Multiscale geometric analysis on the sphere -- Compressed sensing -- This book's take home message.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Transformations (Mathematics); Signal processing; Image processing; Sparse matrices; Wavelets (Mathematics)